(untitled) (Cadernos de Sociomuseologia, 2014)
This text presents a discussion around the ideas of museum planning as a nautical chart. Its aim is to bring the actual debate about museums management for a widest scope of institutions, arguing that small museums should also to include management in their concerns. Methodologically we understand Museology as applied social science, that means it is able to interfere in the reality and also is based in strong theory that should be linked with practices in order to qualify museums and, in the other hand, the reality improve the theory too. Nautical chart need to be flexible as well as museological planning. How Museology can help museums to not be lost in management criterias coming from other areas? Keywords: Museums management, museological planning, Museology, Applied Museology